Revolutions in arthroscopic wrist surgeries. (January 2022) - Nakamura, Toshiyasu; Cheong Ho, Pak; Atzei, Andrea; Corella, Fernando; Haugstvedt, Jan-Ragnar
Recent technical and technological developments in wrist arthroscopic surgery allow for advanced treatments of difficult wrist disorders. In this review, world leaders of wrist arthroscopy describe bone graft for scaphoid nonunion, transosseous repair for triangular fibrocartilage fovea avulsion, palmaris longus reconstruction of the triangular fibrocartilage, and arthroscopic reconstruction of the scapholunate and lunotriquetral ligaments.